APPLICATION OF EXAMPLE NON EXAMPLE LEARNING MODELS IN MATERIALS OF NATIONAL EXAMINATION EVENTS TO IMPROVE STUDENT LEARNING OUTCOMES IN CLASS V SDN 2 BAMBAPULA - Charles Kapile; Isra Malik (Jurnal Dikdas, 2022)
AbstractThe problem in this study is the low student learning outcomes in IPS subjects. The purpose of this study was to improve social studies learning outcomes of class V SDN 2 Bambapula trough  the example non example learning model. This research, which was carried out in class V SDN 2 Bambapula. The subject of this study involved 20 students enrolled in the 2018/2019 shcool year. This study uses a Kemmis and Mc. Taggart research design consisting of two cycles. In each cycle one meeting was held. The result showed pre-action test result with the percentage of classical learning completeness reached 30,0% and classical absorption 59.5%. Cycle I with the acquisition of classical completeness percentage af 65,0% and classical completeness percentage of 90,0% and classical absorption af 82,0%. Teacher activity in cycle 1 reached 72.22% with sufficient criteria, in cycle II an increase of 94,44% with very good criteria. While the activity of students ini cycle I was 70,83% with sufficient criteria, in cycle 2 an increase of 93.05% with very good criteria. It was concluded that the example non example learning model can improve the IPS learning outcomes in the material of national events during the occupation of class V SDN 2 Bambapula.Keywordslearning model, example non example, social studies learning outcomes